Introducing (Re)Imagining AI Interventions /// Intervening (into) AI Imaginaries - Luka, Mary Elizabeth; Zara, Aline; Klimek, Caroline (Imaginations)

(untitled) (York University, 2026)
In this introduction, we share the process of developing this double special issue for Imaginations: from the call for papers to the articles we present in this first special issue volume, and beyond. When we proposed this special issue in 2024, we began by thinking about how to live and work with the rapidly-changing analyses of artificial intelligence softwares, moral panics, and resistances to and takeups of the already-voracious consumption of existing oppressive datasets and social relations. Building on recent work about rebuilding, revisualizing, repairing, or refusing inevitable pathways for AI ubiquity, we were certain we could find other ways of thinking. Drawing from deep scholarly engagement with issues of ethical database scraping and intellectual property violations, environmental impacts, and workflow interferences and augmentations, we asked contributors: What do we/they/you want to happen next? Where do we want to be next year, or five years from now? What are the next 25 years going to look like? The articles we offer in this special issue are mapping and pushing boundaries around the ways we encounter, engage with, and consider the possibilities for AI. This introduction connects these nine articles and how they rethink the world through Indigenous sovereignty, Ubuntu intelligence, speculative methods in policy and practice; and embedded in visual culture sectors through folklore, innovation, labour, archives, and the environment.